Health-related quality of life in children and adolescents with cerebral palsy - Radsel Anja; Osredkar Damjan; Neubauer David (Sciendo, 2017)
In a cross-sectional cohort study, health-related quality of life of Slovenian children and adolescents with cerebral palsy was examined, and factors associated with it have been identified.